The Development of Multiple Intelligence Based Textbook - Suwanto, S; Purba, Azrina (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
This study aims to develop multiple intelligence-based textbooks seventh grade junior high school students with material on equations and inequalities. It is hoped that the results of the development of this textbook can improve student learning outcomes, especially in the ability of mathematical representation. The population used was students of SMP / MTs in Medan, by taking several research samples 108 students. The development model of this textbook uses the 4D development model (define, design, development, Dissemination), but due to the situation during Covid 19 and time constraints it only reaches the development of the expert validation section and limited trials. Thus in this development it only comes to the analysis of validation and practicality of textbooks, but for effectiveness will be continued in next research. The analysis shows that multiple intelligence-based textbooks on equations and inequalities in class VII are declared valid and practical.